STUDY OF THE IMPACT OF TRAINING DESCRIPTION IN EDUCATIONAL ORGANIZATIONS THAT TRAIN MIDDLE-LEVEL SPECIALISTS ON THE NUTRITIONAL BEHAVIOR OF THE STUDENTS - E. V. Izvekova; L. S. Bolshakova; O. L. Ladnova; L. A. Ashikhina; E. G. Merkulova; A. V. Kuzina (Современная наука и инновации)
The purpose of the study was to identify the relationship between nutritional behavior of the students with training description and the awareness level of the students about the principles of healthy lifestyle and proper nutrition. The study included several stages: assessment of the awareness level of young men and women about the principles of healthy lifestyle and proper nutrition, study of the sources of information about rational nutrition and study and identification of nutritional violation of the students. Comparative analysis of indicators was carried out according to training description.